Dependence of brain‐tissue R2 on MRI field strength - Gelderen, Peter; Wang, Yicun; Zwart, Jacco A.; Duyn, Jeff H. (Magnetic resonance in medicine, 2025)
Purpose To quantify T2 relaxation in the brain at 3 T and 7 T to study its field dependence and correlation with iron content, and to investigate whether iron can be separated from other sources of T2 relaxation based on this field dependence. Methods Nine subjects were scanned at both field strengths with the same acquisition technique, which used multiple gradient‐echo sampling of a spin echo. This allowed for separation of T2 relaxation from static dephasing by B0 field inhomogeneities and the effects of radiofrequency refocusing imperfections. The average relaxation rates (R2 = 1/T2) in multiple regions of interest in the brain were fitted with a model linear in B0 and correlated with literature iron values. Results The relationship between the R2 values at the two field strengths appeared to be linear over all regions of interest. The R2 values (in s−1) in the regions of interest for which both an iron and a lipid mass fraction have been documented in the literature were fitted as R2=9+0.9+2·104[Fe]+5.7[lipid]·B0$$ {\mathrm{R}}_2=9+\left(0.9+2\cdotp {10}^4\left[\mathrm{Fe}\right]+5.7\left[\mathrm{lipid}\right]\right)\cdotp {\mathrm{B}}_0 $$, where [Fe]$$ \left[\mathrm{Fe}\right] $$ and [lipid]$$ \left[\mathrm{lipid}\right] $$ indicate the putative mass fractions of iron and lipid. Conclusion The R2 relaxation rate is well described by a constant plus a term linear in B0, with both iron and lipid content contributing to the slope. This indicates that the contributions of lipid and iron to R2 cannot be separated based solely on the field dependence of R2 in the field range of 3–7 T.